Anton Tymofiyovich Brusko - «SISJP NAMS», Staff of SI (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2016)
Article dedicated to the memory of the famous scientist, doctor, public figure, the head of the Pathomorphology Department with experimental biological branch in the Traumatology and Orthopedic Institute of NAMS Professor, Doctor of Medical Sciences Brusko Anton Timofeevich.